Urban street sewer well surface damage repairing material and preparation method thereof

The surface restoration materials of urban street sewer wells prepared by using fast hard sulfaluminate and other materials have been solved in the existing technology, and the problems of long curing time, low strength and poor winter performance have been achieved, and rapid hardening, strength improvement and stable bonding performance have been achieved. The effect of this reduces the cost of urban management and poor aesthetics.

CN119191795APending Publication Date: 2024-12-27INNER MONGOLIA JUSHI MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340419.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing urban street sewer surface repair materials have long curing time, low strength, susceptible to vehicle crushing and damage, inconvenient construction, and deterioration of winter performance, resulting in traffic jams, poor aesthetics, difficult management and high cost.

Method used

Using fast hard sulfaluminate, ordinary silicate cement, natural washing sand, blue gravel, black pigment, crack-resistant glass fiber, carbon nanotube modified bentonite composite repair material, silicone waterproofing agent, silane coupling agent and Materials such as graphene nanosheets are prepared through specific mixing and stirring steps to enhance mechanical properties, water resistance and corrosion resistance, and maintain good performance under low temperature environments.

Benefits of technology

It has achieved rapid hardening of restorative materials, improved strength, stable bonding performance, and safe use in winter, reducing the difficulty and cost of urban management, and improving the aesthetics and attractiveness of urban roads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191795A_ABST
    Figure CN119191795A_ABST
Patent Text Reader

Abstract

The invention discloses an urban street sewer well surface damage repair material and a preparation method thereof, and relates to the technical field of urban infrastructure maintenance, the urban street sewer well surface damage repair material comprises fast hardening sulphoaluminate, ordinary Portland cement, natural washed sand, green gravel, black pigment, an additive and anti-crack glass fiber, the carbon nanotube modified bentonite composite repairing material has the advantages that the carbon nanotube modified bentonite composite repairing material is added into the surface damage repairing material, so that the material can be immersed into an interlayer structure of bentonite, the interlayer spacing of the bentonite is enlarged, harmful substances in the damage repairing material can be effectively adsorbed and fixed, the harmful substances are prevented from polluting the environment, and the service life of the surface damage repairing material is prolonged. The mechanical property and the anti-aging property of the repairing material can be enhanced through high strength and high conductivity of the carbon nano tubes, the repairing material is prevented from being cracked and damaged, and different materials can be tightly connected through chemical bonds in the silane coupling agent by adding the silane coupling agent into the surface damage repairing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of urban infrastructure maintenance, and in particular to a material for repairing surface damage of a sewer well on a city street and a preparation method thereof. Background Art

[0002] The damage of urban street sewers and road surfaces has brought many adverse effects on urban traffic and cityscape, and the existing repair materials have exposed a series of problems that are difficult to ignore in practical applications. From the perspective of time, the long curing time causes the main traffic arteries to be closed for a long time during road repair, which greatly hinders the normal operation of traffic, increases the probability of traffic congestion and accidents, delays people's travel time, and reduces the efficiency of urban traffic. At the same time, the slow strength development makes it difficult for the repaired parts to withstand normal traffic loads in the early stage, and they are prone to being crushed and damaged by vehicles again. Not only do they need secondary or even multiple repairs, but they also waste a lot of manpower, material and financial resources. From the perspective of construction operation, The inconvenience of construction has brought great challenges to the repair work. Some repair materials have strict requirements on the temperature, humidity and other conditions of the construction environment, and are difficult to adapt to the complex and changeable actual construction environment of urban streets. In addition, the complex construction process requires professional equipment and technicians, which not only increases the construction cost, but also prolongs the construction period, affecting the timeliness of urban infrastructure repair. From the perspective of the repair effect, the obvious differences in color, texture and flatness from the original road surface have destroyed the overall aesthetics of the urban road, leaving a bad impression on citizens and tourists, and having a negative impact on the city's image, especially in some key areas and around tourist attractions. Such differences may reduce the city's attractiveness and competitiveness;

[0003] Under the special environment of low temperature in winter, the performance of the repair material further deteriorates, the curing time is greatly extended or even cannot be cured normally, the strength is almost difficult to develop effectively, and the bonding performance drops sharply, resulting in weakened bonding with the original road surface, which is prone to falling off and cracking, making it almost impossible to carry out emergency repair work in winter effectively, seriously affecting the normal use and traffic safety of urban streets in cold seasons, and greatly increasing the difficulty and cost of urban management. For this reason, we propose a surface damage repair material for urban street sewers and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a material for repairing damaged surfaces of urban street sewer wells and a preparation method thereof.

[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solutions: a method for preparing a material for repairing damaged surfaces of urban street sewers, comprising fast-hardening sulphoaluminate, ordinary Portland cement, natural washed sand, blue crushed stone, black pigment, additives and anti-cracking glass fiber, wherein the specific steps of the method for preparing a material for repairing damaged surfaces of urban street sewers are as follows:

[0006] Step 1: Mix the additive and the black pigment to obtain a mixed additive. Avoid water sources during mixing. Sieve the mixed additive and store it in a container after drying and calcining.

[0007] Step 2: Mixing the quick-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair material, avoiding water sources during mixing, to obtain a mixed aggregate, which is stored in a container for later use;

[0008] Step 3: Pour the mixed additive and the mixed aggregate into a mixing container and stir to obtain a mixed repair material. After the mixing is completed, check the bonding state of the mixed repair material. Stir until the powder lumps disappear and then stop stirring.

[0009] Step 4: Add the mixed repair material into a stirring container, and add 10-12 parts of silicone waterproofing agent, 5-15 parts of metakaolin, 10-12 parts of graphene nanosheets and 5-8 parts of bio-based polymer into the stirring container in sequence according to the proportion, stir and mix to form a uniform finished repair material;

[0010] Step 5. After all materials are mixed, they are bagged for later use. When in use, add water to mix them. Monitor the performance of the concrete during the mixing process, adjust the dosage of water reducer and retarder according to actual conditions, and use the slump test to test its fluidity. Put it into use after completion.

[0011] As a further solution of the present invention: in the step 1, the additives include water reducing agent PC-100, water retaining agent HPMC400, defoaming agent PF-07, accelerating setting agent (GL-GF), retarder and anti-cracking glass fiber, and the total components of the additives are 1.7-2.5 parts.

[0012] As a further solution of the present invention: in the step 1, the black pigment is an iron oxide black pigment, and its component is 10-30 parts. After the additive and the black pigment pass through a vibrating screen, they fall into a dryer and are dried at 105°C. After drying, a disperser is used to break them up, and they are transferred to a calcining furnace and calcined at 200°C-220°C for 5min-10min.

[0013] As a further solution of the present invention: in the step 2, the materials and component ratios in the mixed aggregate are 200-350 parts of fast-hardening sulphoaluminate, 100-200 parts of ordinary Portland cement, 200-300 parts of natural washed sand, 300-400 parts of green crushed stone and 200-300 parts of carbon nanotube modified bentonite composite repair material, and the particle size of the green crushed stone is 5mm-10mm.

[0014] As a further solution of the present invention: in the step 2, the carbon nanotube modified bentonite composite repair material and the material are placed in a forced mixer for mixing, and the ambient temperature is controlled at 20°C-25°C. At the beginning, the stirring is carried out at a stirring rate of 50r / min-80r / min for 5 minutes. After the various materials are initially mixed evenly, the stirring is continued at 150r / min-200r / min for 15 minutes. During stirring, the relative humidity of the mixing environment is controlled to be 40%-60%.

[0015] As a further scheme of the present invention: in the step three, ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, kaolin and graphene nanosheets are sieved through 200 mesh-300 mesh, transferred into a drying oven after sieving, and dried at 105°C for 30 minutes. A silane coupling agent is added during drying, and the amount added is 2% of the total mass of all dried materials. The calcination temperature of the fast-hardening sulphoaluminate, ordinary silicate cement and green crushed stone in the calcining furnace is set to 1300°C-1350°C.

[0016] As a further solution of the present invention: In the step 3, the general structural formula of the silane coupling agent is R-SiX3, and when the silane coupling agent undergoes a hydrolysis reaction, the specific reaction equation is as follows:

[0017] R-Si(OCH3)3+3H2O→R-Si(OH)3+3CH3OH

[0018] Where R is an organic functional group, X is a methoxy group -OCH3, and after hydrolysis, silanol undergoes a condensation reaction with the hydroxyl groups on the surface of the material. The specific reaction equation is as follows:

[0019] R-Si(OH)3+M-OH→R-Si-O-M+2H2O

[0020] The M of M-OH is the material, and -OH is the hydroxyl group on the surface of the material.

[0021] As a further solution of the present invention: in the step 4, the graphene nanosheets react with the calcium hydroxide and ettringite in the cement, and the reaction equation is as follows:

[0022] G+xCa(OH) 2 +yA→G-(Ca 2+)m-(OH-)n-(A)p

[0023] Among them, G is graphene nanosheet, A is calcium sulfonate, x, y, m 、 n and p are the stoichiometric coefficients of the reaction.

[0024] The invention discloses a method for preparing a material for repairing the damaged surface of a sewer well on a city street. The material for repairing the damaged surface of a sewer well on a city street comprises quick-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, blue crushed stone, black pigment, additives, anti-cracking glass fiber, carbon nanotube-modified bentonite composite repair material, silicone waterproofing agent, silane coupling agent, metakaolin, graphene nanosheets and bio-based polymers, wherein blue crushed stone, silane coupling agent, anti-cracking glass fiber, carbon nanotube-modified bentonite composite repair material and graphene nanosheets are main additives.

[0025] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:

[0026] 1. The present invention adds a carbon nanotube-modified bentonite composite repair material to a surface damage repair material, so that the material can be immersed in the interlayer structure of bentonite, expand the interlayer distance of bentonite, and effectively adsorb and fix harmful substances in the material in the damage repair material to prevent it from polluting the environment. The high strength and high conductivity of the carbon nanotubes can enhance the mechanical properties and anti-aging properties of the repair material and prevent the cracking and damage of the repair material. By adding a silane coupling agent to the surface damage repair material, different materials can be tightly connected through the chemical bonds therein, thereby improving the interface bonding strength between the materials, which helps to better transfer stress when the repair material is subjected to external force, prevent cracks and delamination, thereby improving the overall mechanical properties of the surface damage repair material, and at the same time improving the water resistance and corrosion resistance of the surface damage repair material. By adding a fast-hardening sulphoaluminate to the surface damage repair material, the surface damage repair material can be quickly hardened when it is put into actual repair operation, and the material can be completely hardened in a short time and can withstand the normal traffic pressure of pedestrians and vehicles.

[0027] 2. The present invention adds black iron oxide pigment to the surface damage repair material, so that the surface of the repaired urban street manholes can be highly integrated with the color of the original road surface. The specially added materials such as graphene nanosheets enhance the stability and durability of the surface damage repair material, and enable it to maintain a good condition for a long time. In the low temperature environment of winter, it can still maintain good performance, and the curing time and strength development are only slightly affected. The bonding performance is stable, so that the repaired surface of the manhole is not prone to falling off and cracking, ensuring the normal use and traffic safety of urban streets in cold seasons. It not only improves the overall aesthetics of urban roads, enhances the attractiveness and competitiveness of the city, but also greatly reduces the difficulty and cost of urban management, and creates a good urban environment for citizens and tourists. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the preparation process of the surface damage repair material in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The present invention discloses a method for preparing a material for repairing damaged surfaces of urban street sewer wells, comprising fast-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, blue crushed stone, black pigment, additives and anti-cracking glass fiber. The method comprises the following specific steps:

[0031] Step 1: Mix the additive and the black pigment to obtain a mixed additive. Avoid water sources during mixing. Sieve the mixed additive and store it in a container after drying and calcining.

[0032] Step 2: Mixing the quick-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair material, avoiding water sources during mixing, to obtain a mixed aggregate, which is stored in a container for later use;

[0033] Step 3: Pour the mixed additive and the mixed aggregate into a mixing container and stir to obtain a mixed repair material. After the mixing is completed, check the bonding state of the mixed repair material. Stir until the powder lumps disappear and then stop stirring.

[0034] Step 4: Add the mixed repair material into a stirring container, and add 10-12 parts of silicone waterproofing agent, 5-15 parts of metakaolin, 10-12 parts of graphene nanosheets and 5-8 parts of bio-based polymer into the stirring container in sequence according to the proportion, stir and mix to form a uniform finished repair material;

[0035] Step 5. After all materials are mixed, they are bagged for later use. When in use, add water to mix them. Monitor the performance of the concrete during the mixing process, adjust the dosage of water reducer and retarder according to actual conditions, and use the slump test to test its fluidity. Put it into use after completion.

[0036] In one embodiment of the present invention: in step one, the additives include water reducing agent PC-100, water retaining agent HPMC400, defoaming agent PF-07, accelerating setting agent (GL-GF), retarder and anti-cracking glass fiber, and the total components of the additives are 1.7-2.5 parts.

[0037] In one embodiment of the present invention: in step one, the black pigment is an iron oxide black pigment, and its component is 10-30 parts. After the additive and the black pigment pass through a vibrating screen, they fall into a dryer and are dried at 105°C. After drying, a disperser is used to break them up, and they are transferred to a calcining furnace and calcined at 200°C-220°C for 5min-10min.

[0038] In one embodiment of the present invention: in step 2, the materials and component ratios in the mixed aggregate are 200-350 parts of fast-hardening sulphoaluminate, 100-200 parts of ordinary Portland cement, 200-300 parts of natural washed sand, 300-400 parts of green crushed stone and 200-300 parts of carbon nanotube modified bentonite composite repair material, and the particle size of the green crushed stone is 5mm-10mm.

[0039] In one embodiment of the present invention: in step 2, the carbon nanotube modified bentonite composite repair material and the material are placed in a forced mixer for mixing, and the ambient temperature is controlled at 20°C-25°C. At the beginning, the stirring is carried out at a stirring rate of 50r / min-80r / min for 5 minutes. After the various materials are initially mixed evenly, stirring is continued at 150r / min-200r / min for 15 minutes. During stirring, the relative humidity of the mixing environment is controlled to be 40%-60%.

[0040] In one embodiment of the present invention: in step three, ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, kaolin and graphene nanosheets are sieved through 200 mesh-300 mesh, transferred into a drying oven after sieving, and dried at 105°C for 30 minutes. During drying, a silane coupling agent is added in an amount of 2% of the total mass of all dried materials. The calcination temperature of fast-hardening sulphoaluminate, ordinary silicate cement and green crushed stone in a calcining furnace is set to 1300°C-1350°C.

[0041] In one embodiment of the present invention: in step 3, the general structural formula of the silane coupling agent is R-SiX3, and when the silane coupling agent undergoes a hydrolysis reaction, the specific reaction equation is as follows:

[0042] R-Si(OCH3)3+3H2O→R-Si(OH)3+3CH3OH

[0043] Where R is an organic functional group, X is a methoxy group -OCH3, and after hydrolysis, silanol undergoes a condensation reaction with the hydroxyl groups on the surface of the material. The specific reaction equation is as follows:

[0044] R-Si(OH)3+M-OH→R-Si-O-M+2H2O

[0045] The M of M-OH is the material, and -OH is the hydroxyl group on the surface of the material.

[0046] In one embodiment of the present invention: in step 4, the graphene nanosheets react with the calcium hydroxide and ettringite in the cement, and the reaction equation is as follows:

[0047] G+xCa(OH) 2 +yA→G-(Ca 2 +)m-(OH-)n-(A)p

[0048] Wherein, G is graphene nanosheet, A is calcium aluminate, and x, y, m, n and p are the stoichiometric coefficients of the reaction.

[0049] In one embodiment of the present invention: the prepared finished repair material is a mixture of solid and powder. When it is needed, the finished repair material and water are mixed and stirred according to the ratio, and the amount of iron oxide black pigment is adjusted according to the actual color of the sewer surface.

[0050] In one embodiment of the present invention: the bio-based polymer is polyhydroxyalkanoate.

[0051] The invention discloses a method for preparing a material for repairing the damaged surface of a sewer well on a city street. The material for repairing the damaged surface of a sewer well on a city street comprises quick-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, blue crushed stone, black pigment, additives, anti-cracking glass fiber, carbon nanotube-modified bentonite composite repair material, silicone waterproofing agent, silane coupling agent, metakaolin, graphene nanosheets and bio-based polymers, wherein blue crushed stone, silane coupling agent, anti-cracking glass fiber, carbon nanotube-modified bentonite composite repair material and graphene nanosheets are main additives.

[0052] Embodiment 1

[0053] Prepare the damaged repair material on the surface of urban street sewers according to the following material ratios:

[0054] Additives (water reducing agent PC-100 accounts for 0.4 parts, water retaining agent HPMC400 accounts for 0.5 parts, defoaming agent PF-07 accounts for 0.3 parts, accelerating setting agent (GL-GF) accounts for 0.5 parts, retarder accounts for 0.3 parts, anti-cracking glass fiber accounts for 0.3 parts, a total of 2.3 parts);

[0055] 20 parts of iron oxide black pigment;

[0056] 300 parts of rapid hardening sulphoaluminate;

[0057] 150 parts of ordinary Portland cement;

[0058] 250 parts of natural washed sand;

[0059] 350 parts of blue crushed stone (particle size 5mm-10mm);

[0060] 250 copies of carbon nanotube modified bentonite composite repair material;

[0061] 11 parts of silicone waterproofing agent;

[0062] 10 parts of metakaolin;

[0063] Graphene nanosheets 11 parts;

[0064] 7 parts of polyhydroxyalkanoate;

[0065] The mixing steps are as follows:

[0066] First, in an independent drying operation room, pour the additive and black pigment into an automatic stirring device, set the stirring speed to 80r / min, and the stirring time to 4min. After the stirring is completed, filter through a 250-mesh screen, spread the filtered material evenly on a drying plate with hot air circulation, and then put it into a drying oven. The temperature of the drying oven is set to 105°C and the drying time is 15min. After the drying is completed, immediately use a high-speed disperser to disperse it at a speed of 1800r / min for 2min, and then transfer it to a calcining furnace. The temperature of the calcining furnace is raised to 210°C and the calcining time is set to 8min. After the calcination is completed, store it in a dry container for use. Quick-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair materials are added to a large forced mixer in turn. At an ambient temperature of 25°C and a relative humidity of 50%, stir it at a stirring rate of 70r / min for 5m in, then increase the stirring rate to 180r / min and continue stirring for 15min. After stirring, transfer the mixed aggregate to a special storage tank for standby use, then screen the ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, kaolin and graphene nanosheets for a second time, the mesh number of the screen is 250 mesh, and the screened material is transferred to a drying oven and dried at 105°C for 30min. During this period, silane coupling agent is added according to 2% of the total mass of all dried materials, and stirred continuously to make it uniformly mixed. After drying, pour it into a high-efficiency mixing device together with the mixed aggregate, stir at a speed of 150r / min, stir until the powder agglomerates disappear, transfer the mixed repair material to a mixing container, add silicone waterproofing agent, kaolin, graphene nanosheets and polyhydroxyalkanoate in order, turn on the stirring device and stir at a speed of 90r / min for 4min to make a uniform finished repair material;

[0067] At an actual urban street sewer construction site, the damaged area is first cleaned and pre-treated to ensure that the surface is flat and free of debris. The finished repair material is then mixed with water in a ratio of 10:1, with the ratio of cement to water being 2.5:1. The mixing time is 3 minutes, and the mixed material is quickly laid on the damaged area and compacted using professional compaction tools. About 18 minutes after laying, the surface of the material begins to gradually harden. After 25 minutes, personnel can walk lightly on its surface without causing obvious damage to the material. After 45 minutes, the material is basically hardened and can withstand a certain amount of vehicle driving pressure. After 95 minutes, the material is completely hardened and can be used for normal traffic.

[0068] Embodiment 2

[0069] Prepare the damaged repair material on the surface of urban street sewers according to the following material ratios:

[0070] Additives (water reducing agent PC-100 accounts for 0.3 parts, water retaining agent HPMC400 accounts for 0.4 parts, defoaming agent PF-07 accounts for 0.2 parts, accelerating agent (GL-GF) accounts for 0.4 parts, retarder accounts for 0.2 parts, anti-cracking glass fiber accounts for 0.2 parts, a total of 1.7 parts);

[0071] Black pigment (iron oxide black pigment) 10 parts;

[0072] 200 parts of rapid hardening sulphoaluminate;

[0073] 100 parts of ordinary Portland cement;

[0074] 200 parts of natural washed sand;

[0075] 300 parts of blue crushed stone (particle size 5mm-10mm);

[0076] 200 copies of carbon nanotube modified bentonite composite repair material;

[0077] 10 parts of silicone waterproofing agent;

[0078] 5 parts of metakaolin;

[0079] 10 parts of graphene nanosheets;

[0080] 5 parts of polyhydroxyalkanoate;

[0081] The mixing steps are as follows:

[0082] In a dry and closed mixing room, add additives and black pigments to a container with a stirring paddle, turn on the stirring paddle and mix at a speed of 60r / min. After stirring evenly, screen through a 200-mesh sieve, and quickly transfer the screened materials to a drying oven. The drying oven has been preheated to 105°C in advance. The materials are taken out after drying for 15 minutes and immediately dispersed at a speed of 1500r / min for 3 minutes using a disperser. Then transfer them to a calcining furnace. The calcining furnace temperature is set to 200°C and the calcination time is 5 minutes. After completion, place them in a sealed container for standby use. In a large forced mixer, pour in fast-hardening sulphoaluminate first, and then add ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair materials in turn. The mixer is stirred at an ambient temperature of 20°C and a relative humidity of 40% for 5 minutes at a stirring rate of 50r / min. After observing that the materials are initially mixed, the stirring rate is increased to 1 50r / min and continue stirring for 15min. After completion, transfer the mixed aggregate to a storage container for standby use. After the ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, metakaolin and graphene nanosheets are sieved again with 200 mesh, transferred to a drying oven and continued to dry at 105°C for 30min. During this process, silane coupling agent is added according to 2% of the total mass of all dried materials. After drying, it is poured into a high-speed mixer together with the prepared mixed aggregate and stirred at a speed of 120r / min. During the stirring process, real-time observation is made. When the powder lumps begin to disappear after stirring, the time is recorded as the 3rd minute after the start. The mixed repair material is quickly transferred to a special container with automatic stirring function, and silicone waterproofing agent, metakaolin, graphene nanosheets and polyhydroxyalkanoate are added in order. The stirrer is turned on and stirred at a speed of 80r / min for 5min to make a uniform finished repair material.

[0083] A damaged area on the surface of a city street sewer was selected for actual repair operations. First, the area was cleaned to remove surface debris and loose parts. Then the finished repair material was mixed with water in a ratio of 10:1, with a cement-to-water ratio of 3:1. The mixing time was 2 minutes. The mixed material was quickly laid on the damaged area and flattened and compacted with tools. Within 15 minutes after laying, it can be clearly observed that the surface of the material began to harden. After 30 minutes, people walking on the surface would basically leave no obvious traces, indicating that the material has a certain strength. After 90 minutes, the material is completely hardened and can withstand the normal traffic pressure of pedestrians and small vehicles.

[0084] Embodiment 3

[0085] Prepare the damaged repair material on the surface of urban street sewers according to the following material ratios:

[0086] Additives (water reducing agent PC-100 accounts for 0.5 parts, water retaining agent HPMC400 accounts for 0.6 parts, defoaming agent PF-07 accounts for 0.4 parts, accelerating agent (GL-GF) accounts for 0.6 parts, retarder accounts for 0.4 parts, anti-cracking glass fiber accounts for 0.4 parts, a total of 2.5 parts);

[0087] Black pigment (iron oxide black pigment) 30 parts;

[0088] 350 parts of rapid hardening sulphoaluminate;

[0089] 200 parts of ordinary Portland cement;

[0090] 300 parts of natural washed sand;

[0091] 400 parts of blue crushed stone (particle size 5mm-10mm);

[0092] 300 copies of carbon nanotube modified bentonite composite repair material;

[0093] 12 parts of silicone waterproofing agent;

[0094] 15 parts of metakaolin;

[0095] 12 parts of graphene nanosheets;

[0096] 8 parts of polyhydroxyalkanoates;

[0097] The mixing steps are as follows:

[0098] In a dry and closed mixing chamber, the additives and black pigment are added to a container with a stirring paddle, and the stirring paddle is turned on to mix at a speed of 80r / min. After stirring evenly, it is screened through a 200-mesh sieve, and the screened materials are quickly transferred to a drying oven, which has been preheated to 105°C in advance. The materials are taken out after drying for 10 minutes, and immediately dispersed at a speed of 1800r / min for 3 minutes using a disperser, and then transferred to a calcining furnace. The calcining furnace temperature is set to 200°C and the calcination time is 10 minutes. After completion, it is placed in a sealed container for standby use. In a large forced mixer, first pour in fast-hardening sulphoaluminate, and then add ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair materials in turn. The mixer is stirred at an ambient temperature of 25°C and a relative humidity of 60% for 5 minutes at a stirring rate of 50r / min. After observing that the materials are initially mixed, the stirring rate is increased to 1 50r / min and continue stirring for 15min. After completion, transfer the mixed aggregate to a storage container for standby use. After the ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, metakaolin and graphene nanosheets are sieved again with 200 mesh, transferred to a drying oven and continued to dry at 105°C for 30min. During this process, silane coupling agent is added according to 2% of the total mass of all dried materials. After drying, it is poured into a high-speed mixer together with the prepared mixed aggregate and stirred at a speed of 120r / min. During the stirring process, real-time observation is made. When the powder lumps begin to disappear after stirring, the time is recorded as the 3rd minute after the start. The mixed repair material is quickly transferred to a special container with automatic stirring function, and silicone waterproofing agent, metakaolin, graphene nanosheets and polyhydroxyalkanoate are added in order. The stirrer is turned on and stirred at a speed of 80r / min for 5min to make a uniform finished repair material.

[0099] A damaged area on the surface of a city street sewer was selected for actual repair operations. First, the area was cleaned to remove surface debris and loose parts. Then the finished repair material was mixed with water in a ratio of 10:1, with the ratio of cement to water being 2.5:1. The mixing time was 2 minutes. The mixed material was quickly laid on the damaged area and flattened and compacted with tools. Within 12 minutes after laying, it can be clearly observed that the surface of the material began to harden. After 35 minutes, people walking on the surface would basically leave no obvious traces, indicating that the material has a certain strength. After 100 minutes, the material is completely hardened and can withstand the normal traffic pressure of pedestrians and small vehicles.

[0100] Hardening time test:

[0101] Use a professional concrete setting time measuring instrument and standard operating methods to lay the mixed repair material in a specific mold according to the construction method in the embodiment. Use a probe to gently touch the surface of the material every 5 minutes to record the time from the beginning of laying of the material to the time when the probe can no longer leave obvious marks on the surface (i.e., initial hardening), and the time when the material can fully withstand a certain pressure (complete hardening);

[0102] Strength detection:

[0103] Compressive strength test: a cubic specimen with a size of 200 mm × 200 mm × 200 mm was made and cured for 2 h under standard curing conditions. The compressive strength test was then performed using a universal testing machine and the data was recorded in MPa.

[0104] Tensile strength test: Use dedicated tensile strength test equipment to make a test piece of a specific shape (such as a dumbbell), perform a tensile test according to the standard test process, and record the tensile strength data in MPa;

[0105] Waterproof performance test:

[0106] Make a 100mm×100mm repair material sheet with a thickness of 20mm, fix it on a test stand with a water injection device, slowly inject water on one side of the sheet to gradually raise the water level, observe whether there is water seepage on the other side, and record the time when water seepage begins under a certain water pressure and the water seepage rate (unit: mL / min). At the same time, use a professional waterproof material permeability tester for accurate testing;

[0107] Adhesion performance test:

[0108] On a simulated surface of a material commonly used in urban street sewers, a layer of repair material prepared according to the proportions of the embodiment was applied. After curing for 2 hours, a pull-out testing machine was used to test the bonding strength. The pull-out force data was recorded, and the bonding strength was calculated based on the contact area of ​​the specimen in MPa.

[0109] The test results are as follows:

[0110] Embodiment 1

[0111] Hardening time: initial hardening time is 18 minutes, and complete hardening time is 95 minutes;

[0112] Compressive strength: The compressive strength reaches 10MPa after 1h of curing, and the compressive strength reaches 25MPa after 24h of curing;

[0113] Tensile strength: After curing for the specified time, the tensile strength is 2.5MPa;

[0114] Waterproof performance: Under 0.5MPa water pressure, a very small amount of water seepage began to appear after 1 hour, and the seepage rate was 0.2mL / min;

[0115] Bonding performance: Bonding strength is 3MPa.

[0116] Embodiment 2

[0117] Hardening time: initial hardening time is 15 minutes, and complete hardening time is 90 minutes;

[0118] Compressive strength: The compressive strength reaches 12MPa after 1h of curing, and the compressive strength reaches 28MPa after 24h of curing;

[0119] Tensile strength: After curing for the specified time, the tensile strength is 2.8MPa;

[0120] Waterproof performance: Under 0.5MPa water pressure, a very small amount of water seepage began to appear after 1.5h, and the seepage rate was 0.15mL / min;

[0121] Bonding performance: Bonding strength is 3.5MPa.

[0122] Embodiment 3

[0123] Hardening time: initial hardening time is 12 minutes, complete hardening time is 100 minutes;

[0124] Compressive strength: The compressive strength reaches 15MPa after 1h of curing, and the compressive strength reaches 30MPa after 24h of curing;

[0125] Tensile strength: After curing for the specified time, the tensile strength is 3.2MPa;

[0126] Waterproof performance: Under 0.5MPa water pressure, a very small amount of water seepage began to appear after 2 hours, and the seepage rate was 0.1mL / min;

[0127] Bonding performance: Bonding strength is 4MPa.

[0128] As the content of each component in the material ratio changes, the strength of the three groups of examples are different. The content of fast-hardening sulphoaluminate, ordinary Portland cement, etc. in Example 3 is relatively high, and its strength is also relatively high, but it will lead to increased costs. It is necessary to find a balance between strength and cost to optimize the material ratio to obtain the best cost-effectiveness.

[0129] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

[0130] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0131] The above contents are merely examples and explanations of the present invention. Various modifications or additions to the specific embodiments described or replacements in similar ways by technicians in the technical field shall fall within the protection scope of the present invention as long as they do not deviate from the invention or exceed the scope defined by the claims.

[0132] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a material for repairing damaged surfaces of urban street sewers, comprising rapid hardening sulphoaluminate, ordinary Portland cement, natural washed sand, blue crushed stone, black pigment, additives and anti-cracking glass fiber, characterized in that: The specific steps of the method for preparing the surface damage repair material of the urban street sewer well are as follows: Step 1: Mix the additive and the black pigment to obtain a mixed additive, and store the mixed additive in a container after drying and calcining; Step 2: Mixing fast-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, green crushed stone and carbon nanotube-modified bentonite composite repair material to obtain a mixed aggregate, which is stored in a container for later use; Step 3, pouring the mixed additive and the mixed aggregate into a mixing container and stirring and mixing to obtain a mixed repair material; Step 4: Add the mixed repair material into a container, add the silicone waterproofing agent, metakaolin, graphene nanosheets and bio-based polymer in sequence, and stir and mix to form a uniform finished repair material; Step 5. After all materials are mixed, they are bagged for later use. When in use, add water to mix them. Monitor the performance of the concrete during the mixing process, adjust the dosage of water reducer and retarder according to actual conditions, and use the slump test to test its fluidity. Put it into use after completion.

2. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step 1, the additives include water reducing agent PC-100, water retaining agent HPMC400, defoaming agent PF-07, accelerating setting agent (GL-GF), retarder and anti-cracking glass fiber, and the total components of the additives are 1.7-2.5 parts.

3. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step 1, the black pigment is an iron oxide black pigment, and its component is 10-30 parts. After the additive and the black pigment pass through a vibrating screen, they fall into a dryer and are dried at 105° C. After drying, a disperser is used to break them up, and they are transferred to a calcining furnace and calcined at 200° C.-220° C. for 5 min-10 min.

4. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step 2, the materials and component proportions in the mixed aggregate are 200-350 parts of fast-hardening sulphoaluminate, 100-200 parts of ordinary Portland cement, 200-300 parts of natural washed sand, 300-400 parts of green crushed stone and 200-300 parts of carbon nanotube modified bentonite composite repair material, and the particle size of the green crushed stone is 5mm-10mm.

5. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step 2, the carbon nanotube modified bentonite composite repair material and the material are placed in a forced mixer for mixing, and the ambient temperature is controlled at 20°C-25°C. At the beginning, the stirring is carried out at a stirring rate of 50r / min-80r / min for 5 minutes. After the various materials are initially mixed evenly, the stirring is continued at 150r / min-200r / min for 15 minutes. During the stirring, the relative humidity of the mixing environment is controlled to be 40%-60%.

6. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step three, ordinary silicate, carbon nanotube modified bentonite composite repair material, additives, kaolin and graphene nanosheets are sieved through 200 mesh-300 mesh, transferred into a drying oven after sieving, and dried at 105°C for 30 minutes. A silane coupling agent is added during drying, and the amount added is 2% of the total mass of all dried materials. The calcination temperature of the fast-hardening sulphoaluminate, ordinary silicate cement and green crushed stone in the calcining furnace is set to 1300°C-1350°C.

7. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In the step 3, the general structural formula of the silane coupling agent is R-SiX3. When the silane coupling agent undergoes a hydrolysis reaction, the specific reaction equation is as follows: R-Si(OCH3)3+3H2O→R-Si(OH)3+3CH3OH Where R is an organic functional group, X is a methoxy group -OCH3, and after hydrolysis, silanol undergoes a condensation reaction with the hydroxyl groups on the surface of the material. The specific reaction equation is as follows: R-Si(OH)3+M-OH→R-Si-O-M+2H2O The M of M-OH is the material, and -OH is the hydroxyl group on the surface of the material.

8. The method for preparing a material for repairing damaged surfaces of urban street sewers according to claim 1, characterized in that: In step 4, the graphene nanosheets react with calcium hydroxide and ettringite in cement, and the reaction equation is as follows: G+xCa(OH) 2 +yA→G-(Ca 2 +)m-(OH-)n-(A)p Among them, G is graphene nanosheet, A is calcium aluminate, and x, y, m'n and p are the stoichiometric coefficients of the reaction.

9. A material for repairing damaged surfaces of urban street sewers applicable to the method for preparing a material for repairing damaged surfaces of urban street sewers according to any one of claims 1 to 8, characterized in that: The preparation materials for the surface damage repair material of the urban street sewer well are fast-hardening sulphoaluminate, ordinary silicate cement, natural washed sand, blue crushed stone, black pigment, additives, anti-cracking glass fiber, carbon nanotube modified bentonite composite repair material, silicone waterproofing agent, silane coupling agent, metakaolin, graphene nanosheets and bio-based polymers, among which blue crushed stone, silane coupling agent, anti-cracking glass fiber, carbon nanotube modified bentonite composite repair material and graphene nanosheets are the main added materials.